Structural and evolutionary insights into astacin metallopeptidases - Gomis-Rüth, F. Xavier; Stöcker, Walter (Frontiers in Molecular Biosciences, 2023)
The astacins are a family of metallopeptidases (MPs) that has been extensively described from animals. They are multidomain extracellular proteins, which have a conserved core architecture encompassing a signal peptide for secretion, a prodomain or prosegment and a zinc-dependent catalytic domain (CD). This constellation is found in the archetypal name-giving digestive enzyme astacin from the European crayfish Astacus astacus. Astacin CDs span ~200 residues and consist of two subdomains that flank an extended active-site cleft. They share several structural elements including a long zinc-binding consensus sequence (HEXXHXXGXXH) immediately followed by an EXXRXDRD motif, which features a family-specific glutamate. In addition, a downstream SIMHY-motif encompasses a ‘Met-turn’ methionine and a zinc-binding tyrosine. The overall architecture and some structural features of astacin CDs match those of other more distantly related MPs, which together constitute the metzincin clan of MPs. We further analysed the structures of pro-, MAM, TRAF, CUB and EGF-like domains, and described their essential molecular determinants. In addition, we investigated the distribution of astacins across kingdoms and their phylogenetic origin. Through extensive sequence searches we found astacin CDs in >25,000 sequences down the tree of life from humans beyond Metazoa, including Choanoflagellata, Filasterea and Ichtyosporea. We also found <400 sequences scattered across non-holozoan eukaryotes including some fungi and one virus, as well as in selected taxa of archaea and bacteria that are pathogens or colonizers of animal hosts, but not in plants. Overall, we propose that astacins originate in the root of Holozoa consistent with Darwinian descent and that the latter genes might be the result of horizontal gene transfer from holozoan donors.